The photographic heritage as a motivational resource to learn and teach history - Ponsoda-López de Atalaya, Santiago; Blanes-Mora, Rubén; Moreno-Vera, Juan Ramón (Frontiers in Education, 2023)
This article, linked to the research of new methods for teaching history, has as its main objective to analyse the motivation of future primary school teachers regarding the use of photographic heritage in the teaching of historical content. This investigation is based on a teaching experience carried out in the 22/23 academic year with 266 primary education student teachers, in which a key episode in the history of Spain is explored via a series of photographs. Data collection was done through a Likert-type questionnaire, which the students answered after the activity, with a response scale of 1 to 4 with some qualitative open-ended questions. Responses were also examined using the SPSS27 statistical programme. The results show how the analysis and interpretation of the photographs, as well as the activities developed from them, are a motivating resource for most of the participants. The latter consider photographs suitable, on the one hand, for their personal development, and on the other, for their professional training, since it allows them to design innovative and creative history teaching-learning programmes 1